GLP‐1 Agonists for Pediatric Psychopharmacology: Opportunities and Cautions - Michael Bartkoski; Ethan A. Poweleit; Stephani L. Stancil (Clinical and Translational Science, 2025)
ABSTRACT Glucagon‐like peptide‐1 agonists (GLP‐1A) are increasingly prescribed to treat obesity and type 2 diabetes mellitus in children and adolescents. Emerging evidence suggesting neuropsychiatric effects presents an opportunity for pediatric psychopharmacology but requires careful consideration of potential adverse effects and risk of misuse. This perspective examines potential applications and cautions surrounding GLP‐1As for pediatric mental health, particularly substance use, depression, and eating disorders, and advocates for research and clinical monitoring to ensure their safety and efficacy.